Bacterial lux-biosensors: Constructing, applications, and prospects - S.V. Bazhenov; U.S. Novoyatlova; E.S. Scheglova; E.V. Prazdnova; M.S. Mazanko; A.G. Kessenikh; O.V. Kononchuk; E.Y. Gnuchikh; Y. Liu; R. Al Ebrahim; G.B. Zavilgelsky; V.A. Chistyakov; et al. (Biosensors and Bioelectronics: X, 2023)
This review aims to systematize data on the construction and applications of bacterial lux-biosensors in various fields ranging from investigation of gene regulation and regulatory networks to the new probiotics' search and ecotoxicological research. The typical technical solutions and devices required for diverse tasks applying lux-biosensors are reviewed. Aspects of the application of lux-biosensors in fundamental researches, such as the study of oxidative stress, heat shock, DNA-damaging, pro- and antioxidant activities, are also considered. This technology allows rapid screening of the biological activities of newly synthesized compounds, which could be applied as components for fuels, household chemicals, and drugs. Works related to the ecological state assessment on water resources are also described. The use of lux-biosensor complexes based on different organisms, including both gram-positive and gram-negative bacteria, makes toxicological investigations more comprehensive. Bacterial lux-biosensors based on Escherichia coli can be used as a model for evaluation of the effect of certain substances on the transmembrane potential in mitochondria, albeit with extrapolation to a certain extent. Another aspect that draws our interest is that biosensors are able to help predict some systemic properties of probiotics. In the future, it's quite promising to see more applications of lux-biosensors for environmental control, microbial-microbial interaction assessment, antioxidant action mechanism studies and toxicological studies in the development of new drugs.